Safety of elvitegravir, cobicistat, emtricitabine, and tenofovir alafenamide in HIV-1-infected adults with end-stage renal disease on chronic haemodialysis: an open-label, single-arm, multicentre, phase 3b trial. Issue 1 (January 2019) - Eron, Joseph J; Lelievre, Jean-Daniel; Kalayjian, Robert; Slim, Jihad; Wurapa, Anson K; Stephens, Jeffrey L; McDonald, Cheryl; Cua, Eric; Wilkin, Aimee; Schmied, Brigitte; McKellar, Mehri; Cox, Stephanie; et al.
Summary: Background: Current treatment for HIV-infected individuals with renal failure on haemodialysis frequently requires complex regimens with multiple pills. A daily single-tablet regimen of coformulated elvitegravir, cobicistat, emtricitabine, and tenofovir alafenamide is approved in Europe, the USA, and in other regions for use in HIV-1-infected individuals with mild-to-moderate chronic kidney disease (creatinine clearance 30–69 mL/min). We aimed to assess the safety, efficacy, and pharmacokinetics of this regimen in HIV-infected adults with end-stage renal disease on chronic haemodialysis. Methods: We did an open-label, single-arm, multicentre, phase 3b trial at 26 outpatient clinics in Austria, France, Germany, and the USA. Participants were HIV-1-infected adults with end-stage renal disease (creatinine clearance <15 mL/min), on chronic haemodialysis for at least 6 months before screening. Virological suppression (ie, plasma HIV-1 RNA <50 copies per mL) on a stable antiretroviral regimen was required for at least 6 months before screening with a CD4 count of at least 200 cells per μL. We switched all participants to coformulated elvitegravir 150 mg, cobicistat 150 mg, emtricitabine 200 mg, and tenofovir alafenamide 10 mg once daily, taken after haemodialysis for up to 96 weeks. We did assessments at study visits at weeks 2, 4, 8, 12, 24, 36, and 48, and every 12 weeks thereafter up to 96 weeks. The primary endpoint was the incidence of treatment-emergent adverse events of grade 3 or higher up to week 48. All participants who received at least one dose of study drug were included in the primary analysis. This study is registered withClinicalTrials.gov (NCT02600819 ) and is closed to new participants. Findings: Between Feb 1, and Nov 3, 2016, 55 participants were enrolled and received at least one dose of study drug. Through week 48, 18 of 55 participants (33%, 95% CI 20–45) had an adverse event of grade 3 or higher on study treatment. Treatment-emergent grade 3 or higher adverse events that occurred in more than one participant included anaemia, osteomyelitis, prolonged electrocardiogram QT, fluid overload, hyperkalaemia, hypertension, and hypotension (all n=2). No adverse event of grade 3 or higher was considered by the site investigators to be treatment related. Three participants (5%, 95% CI 0–11) discontinued treatment because of adverse events; one of these (grade 1 allergic pruritus) was considered treatment related. Treatment-related adverse events were reported for six individuals (11%, 95% CI 3–19), the most common of which was nausea (in four individuals [7%]); all treatment-related adverse events were grade 1 or 2 in severity. Interpretation: At 48 weeks, switching to the single-tablet regimen of elvitegravir, cobicistat, emtricitabine, and tenofovir alafenamide was well tolerated. This regimen might provide a tolerable and convenient option for ongoing treatment of HIV-1 infection in adults with end-stage renal disease on chronic haemodialysis. Funding: Gilead Sciences.